Tomato value chain analysis in Seka Chekorsa District, Jimma Zone, Oromia region, Ethiopia - Zalalam Lule; Mekdelawit Yeshitila; Mulubrihan Bayissa; Fikadu Mitiku (Cogent Food & Agriculture)
Tomato (Lycopersicon esculentum Mill.) is one of edible and nutritious vegetable crops in the world. The objective of this study was to identify tomato value chain actors, their roles and linkages, as well as to estimate the benefit share of tomato value chain actors in Seka Chekorsa District, Jimma Zone and Oromia Region, Ethiopia. Qualitative and quantitative data were collected from primary and secondary sources. Semi structured interview schedules, focus group discussion and key informant interviews were used to collect first-hand information. Two-stage sampling procedure was employed to select 158 tomato producers randomly. Likewise, 20 consumers and 21 Traders were selected randomly and purposively, respectively. To analysis the data, descriptive statistics, value chain mapping and market margin were used. In the study area, the primary tomato value chain actors included input suppliers, producers, local collectors, retailers and consumers. Sinke Bank, Harbu Microfinance, Seka Chekorsa District Agriculture Office, District Trade Office and Non-governmental Organizations were key tomato value chain supporters. There is poor linkage among value chain actors and poor coordination of activities. Producers earned maximum gross profit in channel I (producer–consumer), which was 382.54 birr/qt and the lowest gross profit in channel III (producer–local collectors– retailer–consumer) and channel IV (producer–local collector–consumer), which was 111.07birr/qt. From traders, local collectors took higher gross profit (224.93birr/qt) in channel IV (producer–local collector–consumer). So, it is better for producers to sell their product through channel I (producer–consumer), and imperative to develop ground rules that bind all chain actors together by changing their outlook.